Large-scale InSAR monitoring of permafrost freeze-thaw cycles on the Tibetan Plateau - Daout, S; Doin, M-P; Peltzer, G; Socquet, A; Lasserre, C (American Geophysical Union, 2017)
Multitemporal interferometric synthetic aperture radar (InSAR) observations are used to characterize spatial variations of the permafrost active layer and its temporal evolution in Northwestern Tibet. We develop a method to enhance InSAR performances for such difficult terrain conditions and construct an 8 year timeline of the surface deformation over a 60,000 km2 area. The ground movement induced by the active layer's response to climate forcing is limited to Cenozoic sedimentary basins and is spatially variable in both its seasonal amplitude (2.5–12 mm) and multiannual trend (−2 to 3 mm/yr). A degree‐day integrated model adjusted to the data indicates that subsidence occurs when the surface temperature exceeds zero (May to October) over areas where seasonal movements are large (>8 mm). The period of subsidence is delayed by 1–2 months over areas where smaller seasonal movements are observed, suggesting an unsaturated soil where water occurs in the deeper part of the active layer.